Direct interpretation of the X‐ray and neutron three‐dimensional difference pair distribution functions (3D‐ΔPDFs) of yttria‐stabilized zirconia. Issue 2 (1st March 2023) - Schmidt, Ella Mara; Neder, Reinhard B.; Martin, James D.; Minelli, Arianna; Lemée, Marie-Hélène; Goodwin, Andrew L.
Abstract : Three‐dimensional difference pair distribution functions (3D‐ΔPDFs) from X‐ray and neutron diffraction experiments are used to identify local stabilization mechanisms in yttria‐stabilized cubic zirconia. Abstract : Three‐dimensional difference pair distribution functions (3D‐ΔPDFs) from X‐ray and neutron diffraction experiments are reported for yttria‐stabilized zirconia (Zr0.82 Y0.18 O1.91 ). A quantitative analysis of the signatures in the three‐dimensional difference pair distribution functions is used to establish that oxygen ions neighbouring a vacancy shift by 0.525 (5) Å along ⟨1,  0,  0⟩ towards the vacancy while metal ions neighbouring a vacancy shift by 0.465 (2) Å along ⟨1,  1,  1⟩ away from the vacancy. The neutron 3D‐ΔPDF shows a tendency for vacancies to cluster along ⟨½,  ½,  ½⟩, which results in sixfold coordinated metal ions.